Harassment and obstruction of observers in U.S. fisheries - Jessica L. Dobson; Matthew R. Kahley; Anna M. Birkenbach; Kimberly L. Oremus (Frontiers in Marine Science, 2023)
Fishery observers play a crucial role in the management and conservation of fish stocks, but the treatment they receive aboard fishing vessels can affect their ability to perform their duties. Using law enforcement data from the Northeast and Alaska regions, home to the most important commercial fisheries in the United States, we explore the extent of observer harassment, assault, interference, and obstruction (OHAIO). We find that 16% of 10,346 fishery violations reported in the Northeast and Alaska regions from 2014-2018 are observer-related, and over 80% of those involve OHAIO. We trace how OHAIO incidents are reported and processed and propose steps to mitigate the issue.